TAKAYASU'S DISEASE: ANALYSIS OF CLINICAL AND ANGIOGRAPHIC FEATURES - Shah, Karamat Ali; Awan, Zahid Aslam; Mufti, Waqar A (Journal of Ayub Medical College Abbottabad, 1996)
Analysis of 20 cases of Takamasa's Disease is presented with a view to clinical manifestations and investigations including angiographic findings. There were 15 females and 5 males with a mean age of 21 ±7.1 years (Range 15- 33 years), 90% cases presented with pulselessness while lesion of subclavian arteries was present most frequently (90%). The findings are in conformity with other studies.